Maize potential productivity using simulated climatic data - Assis, Janilson Pinheiro de; Neto, Durval Dourado; Reichardt, Klaus; Manfron, Paulo Augusto; Martin, Thomas Newton; Bonnecarrère, Reinaldo Antônio Garcia (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate a methodology to estimate (proceed referred to obtain the estimated values and the estimative) maize potential productivity according to daily average values of air temperature and solar radiation, using a stochastic model. The values of 86 years for daily average air temperature and 25 years for daily global solar radiation were supplied by Piracicaba Meteorological Station (Esalq/USP). Potential productivity values were simulated 1,000 times for each one of the considered dates of sowing (October 15th, February 15th and August 15th). Two cases for the normal truncated probability distribution were considered (extreme values: average distribution - 1.96 standard deviation and average distribution + 1.96 standard deviation): average temperature daily variable and global solar radiation daily constant, and average temperature daily constant and global solar radiation daily variable. The esteem methodology allows defining the magnitude order of the maize potential productivity for one locality (on the basis of temperature and solar radiation data). The stochastic procedure allows associating maize potential productivity to a probability of occurrence.